ChemInform Abstract: Tunable Color and Energy Transfer in Single‐Phase White‐Emitting Ca20Al26Mg3Si3O68 :Ce3+, Dy3+ Phosphors for UV White Light‐Emitting Diodes. Issue 2 (23rd December 2015) - Yuan, Bo; Song, Yanhua; Sheng, Ye; Zheng, Keyan; Zhou, Xiuqing; Ma, Pingchuan; Xu, Xuechun; Zou, Haifeng
Abstract: Ca20 Al26 Mg3 Si3 O68 :xCe 3+, yDy 3+ (x = 0.02‐0.12; y = 0‐0.09) phosphors are prepared by solid state reaction of CaCO3, Al2 O3, MgO, SiO2, Li2 CO3 (as charge compensator for the lanthanoide dopants), CeO2, and Dy2 O3 in stoichiometric amounts (corundum crucible, 5% H2 /N2, 1400 °C, 2 h).